Seven stages of Lithuanian dialectology - Kardelis, Vytautas (Lietuvių kalba, 2016)
This article is a continuation of ongoing debate on the development of Lithuanian dialectology, the issues of which were first addressed and published in 2015. One of the key ideas expressed by the specialists of dialectology was a proposal to start the development of an extensive model of interests of Lithuanian dialectology. The model could encompass a historical approach, i.e. issues of the development of Lithuanian dialects, essential features of that development as well as the most significant empirical and methodological transformations. The second approach would focus on the perspectives of Lithuanian dialectology which can be placed on the basis of the existing model of interests in Lithuanian dialectology and specific studies carried out in the field. This article proposes a perspective-based plan of research into dialectology and attempts to suggest a tool to implement that plan. The article begins with several introductory remarks about the author’s view towards the existing state of Lithuanian dialectology. It could be briefly described in the following way: traditional dialectology: neogrammarian atomism (exclusive of the theory of dialectology) → structural dialectology: → phonology and natural morphology (inclusive of the theory of phonology and natural morphology but exclusive of the theory of structural dialectology) → the new dialectology: (inclusive of the theory of dialectology: geolinguistics and sociolinguistics, the dynamic socio-cognitive view). The proposed perspective-based plan of research consists of seven stages, namely: typological, varieties (lects) and variants, dialectometry, sociolinguistics and language contacts, perceptive, salience, and empirical. The article does not seek to describe each of the stages in great detail or to review extensive research literature existing on the aspects discussed above. The main aim of this article is to identify and discuss some research trends which are relatively new in Western linguistics and to suggest their application in Lithuanian dialectology. Perhaps this could initiate a discussion among Lithuanian and, possibly, foreign dialectologists working with Lithuanian and Slavic languages with regard to theoretical and methodological issues pertaining to dialectology research. Arguably, the foundation of such a prospective discussion was laid in the work “Lithuanian Dialects of the Early 21st Century: A Geolinguistic and Sociolinguistic Study. Maps and their Commentaries”. Hopefully, this review article will also contribute to the prospective discussions and motivate young researchers of dialects to embark on dialectology research by applying new trends in Lithuanian dialectology.